Drug Release Kinetic Analysis and Prediction of Release Data via Polymer Molecular Weight in Sustained Release Diltiazem Matrices - Adibkia, K.; Ghanbarzadeh, S.; Mohammadi, G.; Khiavi, H. Z.; Sabzevari, A.; Barzegar-Jalali, M. (Drug Research, 2014)
This study was conducted to investigate the effects of HPMC (K4M and K100M) as well as tragacanth on the drug release rate of diltiazem (DLTZ) from matrix tablets prepared by direct compression method.Mechanism of drug transport through the matrices was studied by fitting the release data to the 10 kinetic models. 3 model independent parameters; i. e., mean dissolution time (MDT), mean release rate (MRR) and release rate efficacy (RE) as well as 5 time point approaches were established to compare the dissolution profiles. To find correlation between fraction of drug released and polymer’s molecular weight, dissolution data were fitted into two proposed equations.All polymers could sustain drug release up to 10 h. The release data were fitted best to Peppas and Higuchi square root kinetic models considering squared correlation coefficient and mean percent error (MPE). RE and MRR were decreased when polymer to drug ratio was increased. Conversely, t60% was increased with raising polymer /drug ratio. The fractions of drug released from the formulations prepared with tragacanth were more than those formulated using the same amount of HPMC K4M and HPMC K100M.Preparation of DLTZ matrices applying HPMCK4M, HPMC K100M and tragacanth could effectively extend the drug release.
Keywords: diltiazem; matrix tablets; sustained-release; HPMC; tragacanth; kinetic models